Hipertensión arterial según criterios de la guía americana. sub-centro de salud No.3, Riobamba 2017-2018 - Muñoz Riofrio, Fabián Patricio (2018)
For the development of the proposed research, a descriptive, cross-sectional study will be carried out, with a quantitative-qualitative approach, with the objective of identifying the use of the diagnostic criteria for hypertension offered by the American Association of Arterial Hypertension (Journal of the American Association-JAMA) for the determination of the diagnosis of certainty of this disease in adult and elderly patients treated in the Sub-Center of Health No. 3 of the city of Riobamba, in the period between January 2017 and May of 2018. The totality of clinical histories of adult and elderly patients (287 individuals) diagnosed with HT in the study context will be made up as study population. For the sample selection, a non-probabil istic sampling of the intentional or convenience type will be followed, by means of which the clinical histories of those hypertensive individuals with ages equal to or greater than 40 years, optima!mental health status, residing in the area of influence of the Sub-Center of Health No. 3 of the city of Riobamba and that have been diagnosed during the investigative period (287 patients). Methods of the theoretical level will be used, such as: historical-logical, inductive deductive, theoretical-practical, analytic-synthetic and logical-abstract. As a technique for data collection, a document review guide will be used, which will be validated during the investigative process. This instrument will make it possible to identify the adoption of the diagnostic criteria for arterial hypertension offered by the JAMA for the deter1nination of the diagnosis of certainty of this disease in the individuals carrying this clinical entity in the setting and period of study The analysis of the data will be done using techniques of descriptive statistics, such as distribution of relative and absolute frequencies, which will be collected in a table prepared in Microsoft Excel, to facilitate its processing. The researcher will respect the bioethical principies of scientific research, referring to beneficence, autonomy, j ustice and no maleficence. In addition, the respective authorizations of the representatives of the health institutions in the study context will be obtained.